2018
DOI: 10.1002/pi.5710
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and properties of biodegradable poly(1,4‐butylene adipate) tailored using an aliphatic diamide derivative

Abstract: N,N′‐Ethylenebis(12‐hydroxystearamide) (EBH), an aliphatic diamide organic compound with environmental friendliness, was selected as an effective nucleating agent to be incorporated into poly(1,4‐butylene adipate) (PBA) polyester. EBH increased the crystallization temperature, crystallinity, crystal density and thermal stability, and shortened the crystallization time of PBA. EBH slowed down the critical temperature of the PBA α‐crystal, accelerated the β‐to‐α phase transition rate and tailored the polymorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…It was reported that several multiple amides-containing derivatives as the excellent NAs present outstanding nucleation effect via the hydrogen bond interaction. These NAs not only modulate the polymorphism, tailor mechanical properties, increase melt-crystallization temperature (T c ), crystallization rate, degree of crystallinity (X c ), thermal stability and gas barrier performance, but also induce the crystals to self-assemble into the shish-kebab-like (or cone/needle-like) structures of the isotactic polypropylene (iPP) [28][29][30], poly(L-lactide) (PLLA) [31][32][33][34][35][36][37][38][39][40][41] and poly(1,4-butylene adipate) (PBA) [3,[42][43][44]. Generally, an excellent NA presents a higher T c and melting temperature (T m ) than the polymer matrix because the solidi ed NA crystal can act as the heterogeneous NA on which the molten polymer molecular chains nucleate, before the onset of the crystallization of the polymer [35].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that several multiple amides-containing derivatives as the excellent NAs present outstanding nucleation effect via the hydrogen bond interaction. These NAs not only modulate the polymorphism, tailor mechanical properties, increase melt-crystallization temperature (T c ), crystallization rate, degree of crystallinity (X c ), thermal stability and gas barrier performance, but also induce the crystals to self-assemble into the shish-kebab-like (or cone/needle-like) structures of the isotactic polypropylene (iPP) [28][29][30], poly(L-lactide) (PLLA) [31][32][33][34][35][36][37][38][39][40][41] and poly(1,4-butylene adipate) (PBA) [3,[42][43][44]. Generally, an excellent NA presents a higher T c and melting temperature (T m ) than the polymer matrix because the solidi ed NA crystal can act as the heterogeneous NA on which the molten polymer molecular chains nucleate, before the onset of the crystallization of the polymer [35].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that several multiple amides-containing derivatives as the excellent NAs present outstanding nucleation effect via the hydrogen bond interaction. These NAs not only modulate the polymorphism, tailor mechanical properties, increase melt-crystallization temperature (T c ), crystallization rate, degree of crystallinity (X c ), thermal stability and gas barrier performance, but also induce the crystals to self-assemble into the shish-kebab-like (or cone/needle-like) structures of the isotactic polypropylene (iPP) [28][29][30], poly(L-lactide) (PLLA) [31][32][33][34][35][36][37][38][39][40][41] and poly(1,4-butylene adipate) (PBA) [3,[42][43][44]. Generally, an excellent NA presents a higher T c and melting temperature (T m ) than the polymer matrix because the solidi ed NA crystal can act as the heterogeneous NA on which the molten polymer molecular chains nucleate, before the onset of the crystallization of the polymer [35].…”
Section: Introductionmentioning
confidence: 99%
“…N,N'−ethylenebis (12 − hydroxystearamide) (EBH) is a dispersion agent and diluting agent (with T m ≈ 150°C and T c ≈ 130°C) which are significantly higher than those of the PCL, respectively . Its chemical structure is presented in Scheme .…”
Section: Introductionmentioning
confidence: 99%